Työpankin kautta työllistyminen; Employment Mediation Via Job Banks - Rita Asplund; Antti Kauhanen; Pekka Vanhala (The Research Institute of the Finnish Economy (ETLA), 2016)
– In this report, we follow up the situation of individuals having re-entered the labour market with the help of a so-called job bank. The follow-up period extends over the next two years after their job-bank-mediated transition into the open labour market. We present two different sets of results concerning individuals' near-future labour market experiences. The first set illustrates the development of their employment situation more generally while the second set reports results obtained from using statistical evaluation methods. The results show, inter alia, that the labour market prospects of those having been employed via a job bank have, on average, been clearly better than for identical individuals not having used the services of a job bank.
Keywords: I38; J64; 330; Job bank; Employability; Employment; Active labour market policies; Impact; Evaluation; Arbeitsmarktintegration; Arbeitsvermittlung; Erwerbstätigkeit; Wirkungsanalyse; Finnland